Financial reporting diagnostics for the balance sheet components modeling - Koliesnichenko, Anastasiia; Tkachenko, M. O. (Дніпропетровський державний університет внутрішніх справ, 2023)
The use of financial reporting information allows you to determine the parameters for assessing the financial state of the enterprise, analyzing the results of its activities in order to plan further tasks and strategic guidelines for development. Financial indicators are the main subject of interest for both the internal and external environment of an economic entity. The key element is the economic diagnosis of financial reporting as the most complete and objective source of information about the real economic situation at the enterprise. The purpose of the study is to generalize approaches to the characteristics of types of diagnostics in the economic environment, systematize the methods of economic diagnostics of financial reporting indicators, substantiate the information base for the analysis and financial diagnostics of enterprises, conduct diagnostics of the structure of the balance sheet of the national economy of Ukraine. It has been proven that the important role of economic diagnostics in the management system of the economic entity is due to the existing strategic guidelines, the use of a special methodical apparatus, compliance with legal norms and a high degree of interaction with the implementation of management accounting. In addition, the effectiveness of economic diagnostics in the justification of management decisions depends on the use of various types of models that allow determining and identifying relationships between indicators. The expediency of using the analysis of the dynamics of the balance sheet structure as one of the areas of work with mathematical models of financial diagnostics of macro indicators is substantiated. The practical value of the conducted research lies in the improvement of methodological tools for economic diagnostics of financial reporting indicators of enterprises. The construction of the matrix of the methodical apparatus for the diagnosis of indicators of financial reporting of enterprises made it possible to model the procedure for the diagnosis of economic processes based on the results of the analysis of the structure of the balance of the national economy. Based on the results of the described macro situation, it was determined that the state is recommended to urgently develop an appropriate set of measures aimed at improving the financial condition of enterprises in various fields of activity.

Використання інформації фінансової звітності дозволяє визначити параметри для оцінки фінансового стану підприємства, аналізу результатів його діяльності з метою планування подальших завдань та стратегічних орієнтирів розвитку. Ключовим елементом при цьому стає економічна діагностика фінансової звітності як найбільш повного та об’єктивного джерела інформації про реальну господарську ситуацію на підприємстві. Метою дослідження є узагальнення підходів до характеристики видів діагностики в економічному середовищі, систематизація методів економічної діагностики показників фінансової звітності, обґрунтування інформаційного базису для аналізу і фінансової діагностики підприємств, проведення діагностики структури балансу національної економіки України. Доведено, що вагома роль економічної діагностики в системі управління суб’єкта господарювання обумовлена наявними стратегічними орієнтирами, використанням спеціального методичного апарату, відповідністю нормативно-правовим нормам та високим ступенем взаємодії з впровадженням управлінського обліку. Крім цього, ефективність економічної діагностики при обґрунтуванні управлінських рішень залежить від застосування різних типів моделей, які дозволяють визначити та ідентифікувати зв’язки між показниками. Практична цінність проведеного дослідження полягає в удосконаленні методичного інструментарію економічної діагностики показників фінансової звітності підприємств. Побудова матриці методичного апарату діагностики показників фінансової звітності підприємств дозволила здійснити моделювання процедури діагностики господарських процесів на основі результатів аналізу структури балансу національної економіки. За підсумками описаної макроситуації було визначено, що державі рекомендується терміново розробити відповідний комплекс заходів, спрямованих на покращання фінансового стану підприємств різних сфер діяльності.
Діагностика фінансової звітності при моделюванні складових балансу
Keywords: financial indicators; financial reporting; economic diagnostics; financial results; balance sheet; modeling; фінансові показники; фінансова звітність; економічна діагностика; фінансові результати; баланс; моделювання